A Retrospective Analysis of Thromboembolic Phenomena in Mechanically Ventilated Patients with COVID-19 - Fahad Faqihi; Abdulrahman Alharthy; Abdullah Balhamar; Nasir Nasim; Khaled Alanezi; Feisal Alaklobi; Ziad A. Memish; Mike Blaivas; Saleh A. Alqahtani; Dimitrios Karakitsos (Critical Care Research and Practice)
Background. Recent studies have shown an increased prevalence of thromboembolic disease in critically ill patients with the novel SARS-CoV-2 disease (COVID-19). However, the use of enhanced anticoagulation therapy in these patients remains controversial. Objectives. To determine the incidence of thromboembolic phenomena (TEP) and hemorrhagic events (HEs) in intensive care unit (ICU) COVID-19 patients. Methods. One hundred and sixty ICU patients with COVID-19 were enrolled. Clinical examination results, laboratory data, and imaging studies (computed tomography/Doppler ultrasound scans) for these patients were retrospectively collected and analyzed. Outcome measures including days on mechanical ventilation, ICU length of stay, and day-28 mortality were recorded. Results. Sixty patients (37.5%) developed TEP including thirty patients with deep vein thrombosis, 55 patients with pulmonary embolism, and 7 patients with arterial thromboembolism. Cardiac arrhythmias, lymphocytopenia, and increased D-dimers were more frequently observed in the TEP group compared to the non-TEP group of patients (all p<0.05). The sensitivity, specificity, and positive and negative predictive values of a cutoff D-dimer level of 3.0 μg/mL for predicting PE were 74.5%, 95.1%, 86.8%, and 91.9%, respectively. Thirteen patients experienced HEs, which were more frequently observed in the TEP group (p<0.05). Twenty-eight-day mortality was higher in the TEP group (60%) compared to the non-TEP group (30%) of patients (p=0.02). Conclusions. The rates of TEP and HEs in mechanically ventilated critically ill COVID-19 patients were 37. 5% and 8.1%. Twenty-eight-day mortality was higher in the TEP group (60%) compared to the non-TEP group (30%) of patients.